2023
DOI: 10.5713/ab.22.0277
|View full text |Cite
|
Sign up to set email alerts
|

Genome‑wide identification, organization, and expression profiles of the chicken fibroblast growth factor genes in public databases and Vietnamese indigenous Ri chickens against highly pathogenic avian influenza H5N1 virus infection

Abstract: Objectives: Fibroblast growth factors (FGFs) play critical roles in embryo development, and immune responses to infectious diseases. In this study, to investigate the roles of FGFs, we performed genome-wide identification, expression, and functional analyses of FGF family members in chickens.Methods: Chicken FGFs genes were identified and analyzed by using bioinformatics approach. Expression profiles and Hierarchical cluster analysis of the FGFs genes in different chicken tissues were obtained from the genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In tropical desert climates, a comparative genomics study revealed the presence of advantageous alleles in TLR7 and ZC3HAV1 [10], indicating immune adaptation for defense against zoonotic diseases in chickens [11]. The identi cation of heat shock proteins (HSP) through genome-wide analysis resulted in the discovery of a total of 76 HSP genes [12]. As a cornerstone in chicken genomics research, genome resequencing has provided a roadmap for unraveling the genetic code governing adaptability, disease resistance, and production traits.…”
Section: Introductionmentioning
confidence: 99%
“…In tropical desert climates, a comparative genomics study revealed the presence of advantageous alleles in TLR7 and ZC3HAV1 [10], indicating immune adaptation for defense against zoonotic diseases in chickens [11]. The identi cation of heat shock proteins (HSP) through genome-wide analysis resulted in the discovery of a total of 76 HSP genes [12]. As a cornerstone in chicken genomics research, genome resequencing has provided a roadmap for unraveling the genetic code governing adaptability, disease resistance, and production traits.…”
Section: Introductionmentioning
confidence: 99%